Mapping the anatomical and transcriptional landscape of early human fetal ovary development - Sinead M. McGlacken-Byrne; Ignacio del Valle; Theodoros Xenakis; Ian C. Simcock; Jenifer P. Suntharalingham; Federica Buonocore; Berta Crespo; Nadjeda Moreno; Danielle Liptrot; Paola Niola; Tony Brooks; Gerard S. Conway; et al. (Scientific Reports)
Abstract The complex genetic mechanisms underlying human ovary development can give rise to clinical phenotypes if disrupted, such as Primary (or Premature) Ovarian Insufficiency and Differences of Sex Development. We combine single-nuclei RNA sequencing, bulk RNA sequencing, and micro-focus computed tomography to elucidate the anatomy and transcriptional landscape of the human fetal ovary across key developmental timepoints (Carnegie Stage 22 until 20 weeks post conception). We show the marked growth and distinct morphological changes within the fetal ovary at the critical timepoint of germ cell expansion and demonstrate that the fetal ovary becomes more transcriptomically distinct from the testis with age. We describe previously uncharacterised ovary developmental pathways, relating to neuroendocrine signalling, energy homeostasis, mitochondrial networks, and inflammasome regulation. We define transcriptional regulators and candidate genes for meiosis within the developing ovary. Together, this work advances our fundamental understanding of human ovary development and has relevance for human ovarian insufficiency phenotypes.